DESKRIPSI TENAGA KERJA INDUSTRI KERUPUK RAFIKA - Nurmeitama Indah Wiladatika; Yarmaidi Yarmaidi; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the description of workforce industry in Kerupuk Rafika Industry at Tanjung Harapan subdistrict, South Kotabumi district, North Lampung Regency in the year of 2012, and it focused on the workforce, worker's age, gender, distance between workers’ houses and working location, education level, and income level. In this research, the researcher used descriptive method. The populations of the research all work in Kerupuk Rafika Industry were 20 people.. The primary data collecting techniques were done by observation, interviews, questionnaires, while the secondary data collecting technique was done by documentation. The data analysis of the research was table percentage. The results of this research indicated that: (1) the average age of the workers were 25 years old which were included in productive age.(2) There were 55% or 11 male respondents and there were 45% or 9 female respondents. (3) The average distance between the workers’ houses and working location was 4, 5 km, with the nearest distance 1 km and the farthest distance 10 km. (4) The average education level of the workers in Kerupuk Rafika industry was junior high school. (5) The average income level of the workers in Kerupuk Rafika industry were Rp 567,500,- per month with the highest income Rp 650,000,-per month and the lowest income Rp 450,000,- per month. Key words : Workforce, Age, Distance, Education, Income